2017
DOI: 10.18203/2394-6040.ijcmph20175323
|View full text |Cite
|
Sign up to set email alerts
|

A study to assess the knowledge regarding practices of menstrual hygiene and RTI among high and higher secondary school girls: an educational interventional study

Abstract: Background: Menstruation still a taboo subject to whisper and so, more difficult to discuss the hygiene, practices, perception and myth associated with it. The very ancient socio -cultural restrictions still play a major role in plenty of reproductive tract infections left undiagnosed. Thus resulting in the potential loss of economy in terms of GDP, medical costs, and status of health. The objectives of the study were to assess the awareness, source of information and problems regarding menstrual hygiene at pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 3 publications
1
5
0
1
Order By: Relevance
“…11 Another consistent result showed that 41.1% of them took daily bath. 15 A study done in Mysore, India found 82.9% of respondents cleaned their genitalia every time they visit the toilet, which was nearly similar to the current study result. 5 A study done on field area of Gandhi Medical College, Bhopal showed that 15.7% of respondents washed genitalia with only water which contradicts with present study with 72.6 precentage.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…11 Another consistent result showed that 41.1% of them took daily bath. 15 A study done in Mysore, India found 82.9% of respondents cleaned their genitalia every time they visit the toilet, which was nearly similar to the current study result. 5 A study done on field area of Gandhi Medical College, Bhopal showed that 15.7% of respondents washed genitalia with only water which contradicts with present study with 72.6 precentage.…”
Section: Discussionsupporting
confidence: 88%
“…5 A study done on field area of Gandhi Medical College, Bhopal showed that 15.7% of respondents washed genitalia with only water which contradicts with present study with 72.6 precentage. 15 This discrepancy might be due to difference in geographical variations of the adolescent girls and their accessibility to information through different media regarding menstrual hygiene.…”
Section: Discussionmentioning
confidence: 99%
“…Another barrier to a comfortable and dignified experience of MHM among girls was the lack of or limited awareness as reported in 92 studies (Table 2) [16,18,[23][24][25][26]31,[33][34][35][36][37][39][40][41][42][43][44]48,49,[51][52][53][54][55]57,58,[62][63][64][65][67][68][69][70][71]77,78,[80][81][82][83][84][85]87,89,90,92,93,95,…”
Section: Girls' Awareness Of Mhmmentioning
confidence: 99%
“…(6) In another study done 32.99% girls approved that there is absence of privacy for changing pads while 29.94% responded that there is no space or dustbins for discarding of menstrual pads in school. (7) In majority of cases (62%) information about menstruation was from mother to female teen .while the second majority of information was from friends (30%) and (5%) got information about menses from media like television and newspapers and (3%) got information from relatives. Television programmes about mensuration and menstrual education by trained health care nurses and doctors provide information to Adolescent girls about menstrual hygiene.…”
Section: Issn: 2320-5407mentioning
confidence: 99%